Rewrite the expression as an algebraic expression in x. tan(sin^(-1)(x))

Zackary Duffy 2022-09-13 Answered
Rewrite the expression as an algebraic expression in x.
tan ( sin 1 ( x ) )
You can still ask an expert for help

Want to know more about Trigonometry?

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

trestegp0
Answered 2022-09-14 Author has 12 answers
Given:
tan ( sin 1 ( x ) )
Let sin 1 ( x ) = θ sin θ = x
Therefore,
cos θ = 1 sin 2 θ cos θ = 1 x 2
Put sin 1 ( x ) = θ in equation
tan ( sin 1 ( x ) ) = tan θ tan ( sin 1 ( x ) ) = sin θ cos θ tan ( sin 1 ( x ) ) = x 1 x 2

We have step-by-step solutions for your answer!

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

New questions